No energy, no harvest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The world s energy policies due for a major review by April 2001 have been very, very wrong. Food barely features in them. What shall we eat if we have nothing to harvest? There is a scientific law, the Law of Conservation of Energy, that...